THEORETICAL INVESTIGATIONS OF A DUAL-FUEL LOW-EMISSION GAS TURBINE COMBUSTOR - Diasamidze, Badri Tengizovich; Vilkul, Sergii Volodimirovich; Serbin, Serhiy Ivanovich (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2020)
The use of dual-fuel gas turbine engines is one of the promising direction for improving the efficiency and reliability of power systems. The analysis of the possibility of creating a low-emission dual-fuel combustor for a gas turbine engine has been made. An effective method of organizing the working process in a dual-fuel gas turbine combustor is proposed. A low-emission gas turbine combustor with pre-mixing of fuel and air was selected as a research object. To increase the efficiency of processes in a dual-fuel gas turbine combustor, it is proposed to use the idea of preliminary mixing of liquid fuel with air in axial-radial swirlers. The choice of a mathematical model of liquid fuel burning in a dual-fuel low-emission combustor taking into consideration formation of the main toxic components has been made. Eddy dissipation concept and discrete phase models have been used for liquid fuel combustion process modeling. Theoretical investigations of nitrogen oxides formation have been carried out for various methods of liquid fuel injection into the channels of axial-radial swirlers of low-emission combustor. The results of three-dimensional mathematical modeling showed the prospect of a radial method of liquid fuel injection into the channels of axial-radial swirlers of a gas turbine low-emission combustor in comparison with the traditional method of liquid fuel supply using centrifugal nozzles. The results of mathematical modeling revealed that radial liquid fuel flow improves the thermal and emission combustor’s performance. As result radial fuel supply method was taken as the most efficient and perspective. The calculated values of nitrogen oxides emission at the exit section of the flame tube for radial supply of liquid fuel are 36-46 ppm.